Influence of Product Quality and Service Quality on Purchasing Decisions with Brand Image as an Intervening Variable in International Fast Food Franchise - Meydiana - Suryaningtyas; Winarto - Winarto; Subandi - Subandi (JOBS (Jurnal Of Business Studies), 2022)
This study aims to analyze the influence of product quality and service quality on purchase decision with brand image as intervening variable of fast food franchisee international. There were 100 respondents selected conveniently.  The data collection methods was using questionnaires.  This research uses path analyze with two-stage multiple regression as the analysis method.  Multiple linear regression found that product quality, service quality has a direct effect on purchase decision. Product quality has an indirect effect on purchase decision through brand image. Service quality has an indirect effect on purchase decision through brand image